PERBANDINGAN KINERJA REKSADANA SYARIAH SAHAM DENGAN KINERJA PASAR (ISSI) DI BURSA EFEK - Nur Kholidah (Wahana Islamika: Jurnal Studi Keislaman, 2018)
The purpose of this study is to determine whether there is a difference between the performance of sharia mutual fund shares with market performance by using the Sharpe Method, Treynor, TT Index and MM Index. This study is comparative, IE compares the return rate of sharia mutual fund shares with ISSI index return as a benchmark. The samples taken there are 7 sharia mutual fund shares of the total population of 85 sharia mutual fund shares during the study period. The data used are NAV/investment units of each sharia mutual fund shares, SWBI, and ISSI return. The data are in the form of daily data for 6 months, from October 1, 2015 to March 2016. The results of this study indicate that the Shariah mutual fund performance measured by the Sharpe method during the period October 2015 to March 2016 has a positive performance. Shariah mutual fund performance measured by the Treynor method during the period October 2015 to March 2016 has 6 positive Treynor values ​​and 1 negative Treynor value. Sharia mutual fund performance measured by the TT index method during the period October 2015 to March 2016 has 6 positive TT index values ​​and 1 negative TT index value. Sharia mutual fund performance measured by MM index method during period of October 2015 until March 2016 has MM index positive value, but the return is smaller than market performance return (ISSI).